1992
DOI: 10.2172/6913045
|View full text |Cite
|
Sign up to set email alerts
|

Ecological evaluation of proposed discharge of dredged material from Oakland Harbor into ocean waters (Phase 3 A of -42-foot project)

Abstract: This is Volume 1 of a two-volume report that presents information gathered to determine the suitability of ocean disposal of sediment dredged from Oakland Harbor. This volume contains project background, materials and methods, results, discussions, and conclusions. Volume 2 contains the appendixes (A through S), which provide details of the data analyses and full presentation of the data and results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Phase I evaluated sediments from 20 stations in Oakland Inner Harbor (Word et al 1990a). Phase II of the Oakland Harbor Studies evaluated sediments from six composites in Oakland Inner Harbor and 15 stations in Oakland Outer Harbor (Word et al 1990b). The six composited stations in Oakland Inner Harbor and one station in Oakland Outer Harbor were added to Phase II after it was discovered that coring equipment could not penetrate to the -44-ft project depth at these stationsduring Phase I.…”
Section: 5mentioning
confidence: 99%
See 4 more Smart Citations
“…Phase I evaluated sediments from 20 stations in Oakland Inner Harbor (Word et al 1990a). Phase II of the Oakland Harbor Studies evaluated sediments from six composites in Oakland Inner Harbor and 15 stations in Oakland Outer Harbor (Word et al 1990b). The six composited stations in Oakland Inner Harbor and one station in Oakland Outer Harbor were added to Phase II after it was discovered that coring equipment could not penetrate to the -44-ft project depth at these stationsduring Phase I.…”
Section: 5mentioning
confidence: 99%
“…The six composited stations in Oakland Inner Harbor and one station in Oakland Outer Harbor were added to Phase II after it was discovered that coring equipment could not penetrate to the -44-ft project depth at these stationsduring Phase I. The locations of all sites within Oakland Inner and Outer Harborswhere Word et al (1988Word et al ( , 1990aWord et al ( , 1990bcollected samples for sediment chemistry analyses and bioassays are shown in Figure 3.2.…”
Section: 5mentioning
confidence: 99%
See 3 more Smart Citations